1881 Wash. Sess. Laws 93, An Act to Incorporate the City of Dayton, chap. 2, § 20. - (:unkn) unknown (General Publisher, 1881)
The city of Dayton shall have power to prevent injury or annoyance from anything dangerous, offensive, or unhealthy, and . . . to regulate the transportation, storing and keeping of gunpowder and other combustibles and to provide or license magazines for the same[.]
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER